A Three-User 2x2 MIMO Alamouti/MRC NOMA System Implementation - Ozkan, Lütfullah; Büyükçorak, Saliha; Guven, Eray; Kurt, Gunes Karabulut (IEEE, 2023)
Multi-antenna systems (MIMO) that increase data rate, capacity and performance via diversity schemes, and non-orthogonal multiple access (NOMA) that increases spectral efficiency reveal an important potential for next generation communication systems (5G+). Although there are many efforts on the areas, real-time implementations are quite limited. In this paper, we implement a downlink single hop three-user 2x2 MIMO NOMA system with software defined radio (SDR). The transmitter and receiver diversity schemes are Alamouti that doesn't need channel state information and MRC that provides optimum performance. This paper considers power domain NOMA. The performance of the system is empirically examined over the bit error rate (BER) and outage probability (OP) parameters.
31st IEEE Conference on Signal Processing and Communications Applications (SIU) -- JUL 05-08, 2023 -- Istanbul Tech Univ, Ayazaga Campus, Istanbul, TURKEY
Keywords: Software defined radio; multiple antenna; antenna diversity; non-orthogonal multiple access; multi-user